2008
DOI: 10.1557/jmr.2008.0152
|View full text |Cite
|
Sign up to set email alerts
|

Long-term irradiation effects on gamma-irradiated Nylon 6,12 fibers

Abstract: Long-term effects on Nylon 6,12 crystalline fibers irradiated six years ago have been determined, including chemical structure and morphology, and their relationship with storage time. Results from x-ray diffraction, small-angle x-ray scattering, scanning electron microscopy, and atomic force microscopy are reported for those fibers and for freshly irradiated ones. Some results for non-irradiated samples are included for comparison. Changes in the shape and size of the crystals (crystallinity degree) are found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…This type of degradation coincides very well with other reports [20][21][22][23]. Also, little information is available regarding the post-irradiation effect on polyamides, particularly nylon 6,12 [7,12]. Based on this, the thermal behavior and superficial appearance of freshly irradiated (FI) fibers and fibers gamma-irradiated 6 years previously (6YI) were analyzed, with the aim of obtaining clues on the long-term effect of radiation on these macromolecules, in order to be able to predict their behavior in applications, like reinforcement in mortar and rebar concrete, as protective films, or forming composites or hybrid materials.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…This type of degradation coincides very well with other reports [20][21][22][23]. Also, little information is available regarding the post-irradiation effect on polyamides, particularly nylon 6,12 [7,12]. Based on this, the thermal behavior and superficial appearance of freshly irradiated (FI) fibers and fibers gamma-irradiated 6 years previously (6YI) were analyzed, with the aim of obtaining clues on the long-term effect of radiation on these macromolecules, in order to be able to predict their behavior in applications, like reinforcement in mortar and rebar concrete, as protective films, or forming composites or hybrid materials.…”
Section: Introductionsupporting
confidence: 89%
“…By contrast, there is great interest in studying the radiation stability of polymers [2], as well as the change in chemical, mechanical and physical properties [3], aiming for future applications [4][5][6][7]. However, relatively few reports have been published on the effect of gamma radiation on nylons: mechanical properties [8], melting point decrease [9,10], degree of crystallinity [11][12][13], surface modification [14,15] and additional polymerization [9]. Moreover, there is controversy about the mechanism followed by the gamma-irradiated polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Our main interest consists in grafting polymers onto aggregates surfaces. c) Irradiation -by a variety of sources [12][13][14][15][16][17][18][19]. Gamma irradiation has several advantages over conventional curing processes: I) no catalyst or additives are needed to initiate the reaction; II) the initiation is homogenous throughout the system; III) it can be performed at any temperature and be interrupted at a chosen reaction time; IV) the polymer can be analyzed at selected reaction stages; and V) the temperature during reaction initialization is maintained -as contrasted with highly exothermic curing without irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…In the same work, cross-link is under consideration in the low dose region. An study of the low gamma irradiation dose (up to 50 kGy) has shown that the cross-link process is taking place in the amorphous zone of the nylon 6,12 [Menchaca et al, 2003;Menchaca et al, 2008]. When gamma radiation at low dose is applied both, the fusion temperature and the crystallinity degree show evidence of increments [Thanki et al, 2001], as well as a partial and repairable damage in the amorphous zone, is reported [Malek et al, 2001].…”
Section: Gamma Radiation 92mentioning
confidence: 99%